2022
DOI: 10.3390/ijerph19095185
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Interventions for Post-Acute COVID-19 Syndrome: A Systematic Review

Abstract: Increasing numbers of individuals suffer from post-acute COVID-19 syndrome (PACS), which manifests with persistent symptoms, the most prevalent being dyspnea, fatigue, and musculoskeletal, cognitive, and/or mental health impairments. This systematic review investigated the effectiveness of rehabilitation interventions for individuals with PACS. We searched the MEDLINE, Embase, Cochrane Register of Controlled Trials, CINHAL, Scopus, Prospero, and PEDro databases and the International Clinical Trials Registry Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
116
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 35 publications
5
116
0
13
Order By: Relevance
“…Different rehabilitation strategies have been proposed to improve the functions and the quality of life of patients suffering from COVID-19 infection both in the acute [68] and the chronic phase [69]. In the acute phase, rehabilitation seemed to improve dyspnoea, anxiety, and kinesiophobia.…”
Section: Rehabilitation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different rehabilitation strategies have been proposed to improve the functions and the quality of life of patients suffering from COVID-19 infection both in the acute [68] and the chronic phase [69]. In the acute phase, rehabilitation seemed to improve dyspnoea, anxiety, and kinesiophobia.…”
Section: Rehabilitation Strategiesmentioning
confidence: 99%
“…In the acute phase, rehabilitation seemed to improve dyspnoea, anxiety, and kinesiophobia. Results on pulmonary function were inconsistent, while improvements were detected in muscle strength, walking capacity, sit-to-stand performance, and quality of life, no information was available for cognitive functions [68].…”
Section: Rehabilitation Strategiesmentioning
confidence: 99%
“…A systematic review of five randomised controlled trials confirmed that rehabilitation could improve dyspnoea, muscle strength, walking capacity, sit-to-stand performance, anxiety and quality of life of patients with COVID-19 13. Rehabilitation therapies should be carried out as early as possible to reduce the complications and disability rate and improve the patients’ overall function at different stages of COVID-19 5 14 15.…”
Section: Introductionmentioning
confidence: 98%
“…Early intervention has indeed been shown to be effective to reduce the risk of long COVID [ 19 ]. Different rehabilitation strategies have been proposed to enhance the function and quality of life of COVID-19-infected patients in the acute phase [ 20 ]. Rehabilitation appeared to improve dyspnea, anxiety, and kinesiophobia during the acute phase.…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation appeared to improve dyspnea, anxiety, and kinesiophobia during the acute phase. Inconsistent results were observed for pulmonary function, whereas improvements were observed in muscle strength, walking capacity, sit-to-stand performance and quality of life [ 20 ].…”
Section: Introductionmentioning
confidence: 99%